Designing E-Learning-Based IPAS Learning Tools Using Flipbook Media - Leni Zahara; Atika Ulya Akmal; Yesni Yenti; Salamaini Salamaini; Indri Fitriyanni (Jurnal Penelitian Pendidikan IPA, 2026)
IPAS learning in elementary schools, which integrates natural and social science content, requires innovative learning media that support interactive, contextual, and digital-based learning in accordance with the Merdeka Curriculum. However, learning tools used by teachers are still limited and have not optimally utilized e-learning media. Digital learning media is a technology-based means that allow the presentation of information in a multimodal manner through text, images, audio, video, animation, and interactivity. This study aims to describe the process of designing e-learning-based IPAS learning tools for Grade V elementary school using flipbook media based on the teaching module “How to Form My Indonesia”, which emphasizes geographical content. This research employed a qualitative descriptive approach through several stages, including teaching module analysis, content design, learning tool structuring, and flipbook media development. Data were obtained through document analysis and the study of learning characteristics of elementary IPAS. The results indicate that the designed flipbook integrates learning objectives, core learning activities, learning videos, digital worksheets (LKPD), and assessments in a structured and interactive format. The flipbook facilitates teachers in delivering material and supports students’ independent learning. This design contributes to improving the quality of e-learning-based IPAS learning in elementary schools.